2005
DOI: 10.1530/eje.1.01895
|View full text |Cite
|
Sign up to set email alerts
|

Hypopituitarism after traumatic brain injury

Abstract: Traumatic brain injury (TBI) is one of the main causes of death and disability in young adults, with consequences ranging from physical disabilities to long-term cognitive, behavioural, psychological and social defects. Post-traumatic hypopituitarism (PTHP) was recognized more than 80 years ago, but it was thought to be a rare occurrence. Recently, clinical evidence has demonstrated that TBI may frequently cause hypothalamic -pituitary dysfunction, probably contributing to a delayed or hampered recovery from T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
152
0
29

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 185 publications
(184 citation statements)
references
References 101 publications
3
152
0
29
Order By: Relevance
“…High levels of IL-6 in plasma and liquor are found after TBI. (3) IL-6 might stimulate vasopressin secretion and may be involved in the pathogenesis of the syndrome of inappropriate hormone secretion (ADHantidiuretic hormone) after TBI (61) .…”
Section: Inflammatory Markersmentioning
confidence: 99%
See 4 more Smart Citations
“…High levels of IL-6 in plasma and liquor are found after TBI. (3) IL-6 might stimulate vasopressin secretion and may be involved in the pathogenesis of the syndrome of inappropriate hormone secretion (ADHantidiuretic hormone) after TBI (61) .…”
Section: Inflammatory Markersmentioning
confidence: 99%
“…(77) The pituitary gland responds to acute traumatic events and many changes in hormone levels become apparent in the first hours or days after trauma. (61,78) Recent studies have shown that various inflammatory mediators including cytokines and free radicals may affect endocrine function at the acute stage of TBI. (78) Such changes represent part of the acute adaptive response to trauma and may also be influenced buy medication administered at this stage such as glucocorticoids, narcotics or dopaminergic agents.…”
Section: Neuroendocrine Markersmentioning
confidence: 99%
See 3 more Smart Citations